(untitled) (REMUNOM, 2023)
The purpose of this study was to demonstrate the importance of early diagnosis of oral cancer, especially in the elderly. Its high occurrence, around more than 90%, are the following types: Squamous Cell Carcinoma (SCC), where the most affected areas are the lateral and posterior margin of the tongue, the oral floor and the lower lip. It is essential to take preventive actions of this disease and demonstrate the elements of risk that contribute to its development. The individuals most affected by cancer in general are the elderly, due to cellular aging and the lower condition of the cells to reestablish. Oral cancer found in the initial stage leads to early treatment, reducing the chances of emergence of related diseases, and also the death of these people.